Association Between Plasma Caffeine and Other Methylxanthines and Metabolic Parameters in a Psychiatric Population Treated With Psychotropic Drugs Inducing Metabolic Disturbances - Delacrétaz, Aurélie; Vandenberghe, Frederik; Glatard, Anaïs; Levier, Axel; Dubath, Céline; Ansermot, Nicolas; Crettol, Séverine; Gholam-Rezaee, Mehdi; Guessous, Idris; Bochud, Murielle; von Gunten, Armin; Conus, Philippe; et al. (Frontiers in Psychiatry, 2018)
Importance: Multiple studies conducted in the general population identified an association between self-reported coffee consumption and plasma lipid levels. To date, no study assessed whether and which plasma methylxanthines (caffeine and/or its metabolites, i.e. paraxanthine, theophylline and theobromine) are associated with plasma lipids. In psychiatric patients, an important coffee consumption is often reported and many psychotropic drugs can induce a rapid and substantial increase of plasma lipid levels. Objective: To determine whether plasma methylxanthines are associated with metabolic parameters in psychiatric patients receiving treatments known to induce metabolic disturbances. Design, Setting and Participants: Data were obtained from a prospective study including 630 patients with metabolic parameters (i.e. body mass index [BMI], total cholesterol [TC], low-density lipoprotein cholesterol [LDL-C], high-density lipoprotein cholesterol [HDL-C], non–high-density lipoprotein cholesterol [non-HDL-C], and fasting triglycerides [TG]) monitored routinely during psychotropic treatment. Exposures: Plasma methylxanthines levels. Main Outcomes and Measures: Metabolic variables including BMI and plasma lipid levels. Results: Multivariate analyses indicated that BMI, TC, HDL-C and non-HDL-C increased significantly with increasing total methylxanthines (pcorrected≤0.05). In addition, compared to patients with plasma caffeine concentration in the lowest quartile, those with caffeine concentration in the highest quartile were twice more prone to suffer from non-HDL hypercholesterolemia (pcorrected=0.05), five times more likely to suffer from hypertriglyceridemia (pcorrected=0.01) and four times more susceptible to be overweight (pcorrected=0.01). Conclusions and Relevance: This study showed that plasma caffeine and other methylxanthines are associated with worsening of metabolic parameters in patients receiving psychotropic treatments known to induce metabolic disturbances. It emphasizes that important caffeine consumption could be considered as an additional environmental risk factor for metabolic worsening in patients receiving such treatments.